2016
DOI: 10.17221/425/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Phosvitin phosphopeptide preparation using immobilised trypsin and enhancing calcium absorption in growing rats

Abstract: We demonstrate a new, efficient method for the preparation of phosvitin phosphopeptides using immobilised-trypsin enzymolysis technology. Immobilised trypsin was prepared using a covalent binding method, and then was added to degrade egg yolk phosvitin for the production of phosphopeptides. In our results, the prepared immobilised trypsin demonstrated a higher hydrolysing activity toward phosvitin than free trypsin, and the hydrolysing activity was retained well even after trypsin was repeatedly used up to fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…CPPs are commercially available for use in milk-based formula as dietary carriers of calcium and other divalent minerals due to the presence of a unique cluster of three phosphorylated serine residues and two glutamate residues [ 60 ]. Egg yolk also contains phosphorylated protein, like phosvitin, which was used to produce phosphopeptides with a binding capacity towards calcium and improve bioavailability [ 61 ].…”
Section: Hydrolyzed Food Proteins and Peptides That Chelate Or Enhmentioning
confidence: 99%
“…CPPs are commercially available for use in milk-based formula as dietary carriers of calcium and other divalent minerals due to the presence of a unique cluster of three phosphorylated serine residues and two glutamate residues [ 60 ]. Egg yolk also contains phosphorylated protein, like phosvitin, which was used to produce phosphopeptides with a binding capacity towards calcium and improve bioavailability [ 61 ].…”
Section: Hydrolyzed Food Proteins and Peptides That Chelate Or Enhmentioning
confidence: 99%
“…Since enzymatic hydrolysis to generate phospho-peptides would likely avoid the perceived pitfalls of native phosvitin, PPPs are a possible approach to enhancing osteogenic and/or osteoprotective functions. Previous studies have also suggested that PPPs show enhanced bioactivities (anti-inflammation, antioxidant and calcium absorption promoting) compared to native phosvitin [ 43 , 44 ], further supporting the role(s) of phosphorylation in bioactive properties. In contrast, bioactive peptides lacking of phosphorylation, such as LRW derived from pea protein [ 45 ], VLPVPQK, EDVPSER, NAVPITPTL, HPHPHLSF derived from buffalo casein [ 46 ], YVEEL and YLLF derived from whey proteins [ 47 ], and IRW from egg proteins [ 48 ], were also reported to promote the proliferation of MC3T3-E1 cells, but they may not be as resistant to digestion as phospho-peptides, which therefore limits their potential applications [ 42 ].…”
Section: Discussionmentioning
confidence: 71%
“…Serum calcium levels (SCL) can serve as a valid indicator of whether an active substance has a pro-calcium absorption effect. For example, SCL in mice were found to be significantly increased after they were administered calcium phosphopeptide chelates [ 97 ]. Similar results were found in a study about the bioactivities of calcium herring egg phosphopeptides chelates.…”
Section: Bioavailability Of Calcium–peptide Chelatesmentioning
confidence: 99%